Intestinal complications are common in patients with acquired diaphragmatic hernia after pediatric living donor liver transplantation. (8th December 2021) - Seda Neto, João; M. Costa, Carolina; Fonseca, Eduardo A.; Vincenzi, Rodrigo; Pugliese, Renata; Rocha, João Ivo X.; Roda, Karina; Benavidez, Marcel R.; Oliveira, Caio Márcio V.; Pereira, Fabio Payão; Assis, André Moreira; Feier, Flavia H.; et al.
Abstract: Background: Acquired diaphragmatic hernia (DH) following liver transplantation (LT) is usually considered a surgical emergency. Interplay of contributing elements determines its occurrence but, in children, LT with partial liver grafts seems to be the most important causative factor. Methods: This retrospective study describes the clinical scenario and outcomes of 11 patients with acquired DH following LDLT. Results: During the study period, 1109 primary pediatric LDLT were performed (0.8% DH). The median age and BW of the recipients with DH at transplantation were 17 months and 11.1 kg, respectively; 63.7% of the cases had a weight/age Z‐score of less than −2 at transplantation. The median interval between transplantation and diagnosis of DH was 114 days (32–538 days). A total of 6 (54.5%) of the patients had bowel obstruction due to bowel migration into the hemithorax. Ten defects were right‐sided. Three patients required enterectomy and enterorrhaphy. Two patients required a new bilioenteric anastomosis, and one of them had complete necrosis of the Roux‐in‐Y limb. The patient with left‐side DH presented gastroesophageal perforation. Conclusion: Most defects necessitate primary closure as the first treatment, and recurrence is rare. The associated problems encountered, especially related to intestinal complications, can determine increased morbidity following DH repair. Early diagnosis and intervention are required for achieving better outcomes.